Information Systems to Enhance Focus in the Learning Process Using Design Thinking Methodology - Wahyu Rahayu; Aji Primajaya (LPPM Universitas Bina Sarana Informatika, 2023)
This study adopts the Design Thinking methodology to investigate the habits, needs, and challenges faced by students when attempting to maintain focus during activities that require concentration. The research surveyed students, with a significant proportion (approximately 53% of all participants) reporting frequent loss of focus during tasks. External disturbances, such as an unconducive environment, gadget notifications, and enticing distractions, were identified as the primary triggers for this lack of focus, resulting in procrastination and hindrance in achieving their main goals. In response to these findings, this research proposes a User Interface / User Experience (UI/UX) design approach to develop an application aimed at enhancing focus and learning performance to boost overall productivity. The design aims to ensure the application's interface is user-friendly and easily comprehensible. By designing an application interface that can organize focused sessions for the activities to be carried out by the users. The UI/UX design of this application holds the potential to empower students in elevating their learning experience, thereby fostering higher productivity and goal achievement. The results of this research show that the use of the Design Thinking methodology achieved a score of 70% from the overall users who tested the application design using the Maze tool.